FnCas12a/crRNA-Mediated Genome Editing in Eimeria tenella - Cheng, Peipei; Zhang, Zhihao; Yang, Fayu; Cai, Shuo; Wang, Lina; Wang, Chunmei; Wang, Mi; Liu, Yingchun; Fei, Chenzhong; Zhang, Lifang; Xue, Feiqun; Gu, Feng (Frontiers in Genetics, 2021)
Eimeria species are intracellular parasites residing inside the intestinal epithelial cell, which cause poultry coccidiosis and result in significant financial losses in the poultry industry. Genome editing of Eimeria is of immense importance for the development of vaccines and drugs. CRISPR/Cas9 has been utilized for manipulating the genome of Eimeria tenella (E.tenella). Ectopic expression of Cas9, i.e., via plasmids, would introduce transgene, which substantially limits its application, especially for vaccine development. In this study, we initially optimized the condition of the transfection protocol. We demonstrated that with the optimized condition, the transfection of FnCas12a (also known as “FnCpf1”) protein and crRNA targeting EtHistone H4 triggered DNA double-strand breaks in vivo. We then used this strategy to knock-in a coding cassette for an enhanced yellow fluorescent protein (EYFP) and dihydrofolatereductase thymidylatesynthase gene (DHFR) as a selection marker to tag endogenous EtActin. The engineered E.tenella parasite possesses EYFP expression in its entire life cycle. Our results demonstrated that FnCas12a could trigger genome editing in E.tenella, which augments the applicability of the dissection of gene function and the development of anticoccidial drugs and vaccines for Eimeria species.